Español Español: English - Talledo, David (2023)
Objectives: To propose the use of artificial intelligence to partially reduce uncertainty when investing in the stock market. To demonstrate, through the use of fuzzy logic, that with this proposal it is possible to obtain positive results and high profitability. Methods: The research approach is quantitative experimental and quali-quantitative descriptive; micro and macroeconomic information is taken to experiment with a stock of the Lima Stock Exchange. Quali-quantitative results from previous research are analyzed. Results: It is demonstrated that it is possible to use artificial intelligence to make better investments in the Stock Exchange. In addition, high profitability is obtained in the experiment. Conclusions: The use of artificial intelligence and, specifically, a fuzzy logic algorithm, is effective in conveying knowledge, experience and reducing uncertainty when investing in different financial markets. However, there is still much to be developed in this area and no algorithm should be considered infallible. Keywords: Data Science; Fuzzy Logic; Stock Exchange; Investment.